A PROBLEM-BASED LEARNING MODEL IN BIOLOGY EDUCATION COURSES TO DEVELOP INQUIRY TEACHING COMPETENCY OF PRESERVICE TEACHERS - Aryulina, Diah; Riyanto, Riyanto (LPMPP Universitas Negeri Yogyakarta, 2016)
Abstract: This study was aimed to: 1) develop a problem-based learning model in the Biologyy education, and 2) obtain the expert evaluation on the appropriateness of the developed model. The model was developed using the instructional design system approach based on the analysis of Biology teachers’ needs, and literary study on the characteristics and process of the problem-based teaching. The evaluation of the model was done by two experts at Biology education. The data obtained from the evaluation were analyzed descriptively. The structure of the developed model in the courses of Biology Teaching Strategies, Micro Teaching, and Teaching Practicum consisted of the following stages: identification of the problems, plan of the problem solving, implementation of the problem solving, presentation of the problem solving result, and reflection of the problem solving. Those five stages were carried out repeatedly in several cycles. The result of the expert evaluation showed that the developed model was in accordance with the characteristics of the problem-based teaching and was appropriate to be used to develop the inquiry teaching competency of preservice teachers. Key words: PBL model, biology education courses, preservice teachers, inquiry teaching competencyMODEL PEMBELAJARAN BERBASIS MASALAH PADA MATAKULIAH PENDIDIKAN BIOLOGI UNTUK MENGEMBANGKAN KOMPETENSI PEMBELAJARAN INKUIRI Abstrak: Tujuan tahap awal penelitian pengembangan ini adalah: 1) mengembangkan model pembelajaran berbasis masalah (PBM) pada matakuliah pendidikan biologi, dan 2) memeroleh penilaian ahli terhadap ketepatan model PBM. Model PBM dikembangkan menggunakan pendekatan sistem desain instruksional berdasarkan analisis kebutuhan kompetensi guru biologi, serta kajian literatur mengenai ciri dan proses pembelajaran berbasis masalah. Evaluasi model PBM dilakukan oleh dua pakar pendidikan biologi. Selanjutnya data evaluasi dari pakar dianalisis secara deskriptif. Struktur model PBM yang dikembangkan pada matakuliah Strategi Pembelajaran Biologi, PPL I, dan PPL II terdiri atas tahap identifikasi masalah, perencanaan pemecahan masalah, pelaksanaan pemecahan masalah, penyajian hasil pemecahan masalah, dan refleksi pemecahan masalah. Kelima tahap tersebut dilaksanakan berulang dalam beberapa siklus selama semester. Hasil penilaian pakar menunjukkan bahwa model PBM sesuai dengan ciri pembelajaran berbasis masalah dan tepat digunakan untuk mengembangkan kompetensi pembelajaran inkuiri calon guru. Kata kunci: Model PBM, matakuliah pendidikan biologi, calon guru, kompetensi pembelajaran inkuiri